Photodynamic Action of Synthetic Curcuminoids against Staphylococcus aureus: Experimental and Computational Evaluation - Melo, Nícolas J. (2024)
Natural curcumin is composed of three curcuminoids, namely curcumin (CUR), deme-thoxycurcumin (DMC) and bis-demethoxycurcumin (BDMC). These compounds are utilized in various biophotonics applications, including photodynamic therapy (PDT). This work aimed to evaluate the photodynamic action (alternative to antibiotics) of synthetic curcuminoids against Staphylococcus aureus. Herein, we evaluated an optimal proportion of the three curcuminoids mixed in solution to improve photoinactivation effects. Therefore, a set of computational calculations was carried out to understand the photodynamic action (stability and mechanism) of curcuminoids. Regarding computational analysis, the curcuminoid molecules were optimized using DFT with the hybrid exchange–correlation functional M06-2X, which includes long-range correction, and the 6-311++G(d,p) basis set. DMC and BDMC were more effective as photosensitizers than curcumin at a very low concentration of 0.75 µM, inactivating more than five orders of magnitude of S. aureus. Theoretical UV-vis absorption spectra showed that at maximum absorption wavelengths, electronic transitions of the π→π* type originated from H→L excitations. The BDMC was more stable than the other two curcuminoids after photobleaching, and the fluorescence emission was also higher, which could lead to its usage as a fluorescence dye to track bacteria. In fact, the results of electronic structure calculations proved that the stability order of curcuminoids is CUR < DMC < BDMC. The mixture of synthetic curcuminoids was more effective in the inactivation of S. aureus compared to curcumin by itself; for all proposed mixtures, an equal or superior reduction was achieved.